EVALUASI EKONOMI DALAM PENYULUHAN KESAHATAN - Hairun Nisa; Abi Burrahman; Adinda Maulida; Sahidun; M. Yuza Royandi; Yogi Andreawan; Lale Ajeng Khalifatun Wardani (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2022)
Economic problems always attract great attention of individuals or society especially in health. Various ways have been done by the government to solve the problem. This article aims to explore economic evaluation on health counseling. This article is a research based on a literature review using the library method. The results show that the economic analysis of public health programs is generally identified by calculating the value of money. One of the limitations of economic analysis is that it does not take into account the value of the pain or suffering experienced in terms of money.